A Pugh Matrix based product development model for increased small design team efficiency. Issue 1 (1st January 2021) - Guler, Kutay; Petrisor, Denisa Mirela
Abstract: This study proposes a new product development model for small design teams with limited resources, based on the Pugh Matrix. The purpose is to address the various known shortcomings of Pugh Matrix by providing the ability to logically define criteria relationships and weightings and by evaluating new concepts against chosen reference solutions per criterion instead of evaluating against discrete products, thus increasing team effectiveness. The practicality of the proposed model was investigated through a case study, development of a contemporary wall tile based on the traditional Turkish ceramic designs. Findings indicated that a systematic exploratory phase enhanced the understanding of the design problem and its constituents, contributed to the design team's overall efficacy; the utilization of iterative evaluations revealed the strengths and deficiencies of each design alternative in terms of criteria groups as well as individual criteria; the ability to track criteria relationships revealed the possible impacts of each design decision.